Griffithsin, a Highly Potent Broad-Spectrum Antiviral Lectin from Red Algae: From Discovery to Clinical Application - Choongho Lee (Marine Drugs, 2019)
Virus entry into a susceptible host cell is the first step in the formation of all viral diseases. Controlling viral infections by disrupting viral entry is advantageous for antibody-mediated neutralization by the host’s immune system and as a preventive and therapeutic antiviral strategy. Recently, several plant-derived carbohydrate-binding proteins (lectins) have emerged as a new class of antiviral biologics by taking advantage of a unique glycosylation pattern only found on the surface of viruses. In particular, a red algae-derived griffithsin (GRFT) protein has demonstrated superior in vitro and in vivo antiviral activity with minimum host toxicity against a variety of clinically relevant, enveloped viruses. This review examines the structural characteristics of GRFT, focusing on its carbohydrate-binding capability. Its in vitro antiviral profiles against human immunodeficiency virus (HIV) are also discussed followed by a description of the results from a combination study using anti-HIV drugs. The results of several studies regarding its novel antiviral mechanism of action are provided in conjunction with an explanation of viral resistance profiles to GRFT. In addition, its in vitro and in vivo host toxicity profiles are summarized with its pharmacokinetic behavior using in vivo efficacy study results. Also, a large-scale production and formulation strategy, as well as a drug delivery strategy, for GRFT as a new class of broad-spectrum microbicides is discussed. Finally, results from two ongoing clinical studies examining GRFT’s effects on viruses are presented.